CHILDREN UNDER THE THREAT OF LEPROSY: TRANSMISSION AND HANDLING IN DUTCH COLONIAL EAST INDIES IN THE EARLY 20TH CENTURY - Wulandari, Ayu (Kementerian Pendidikan dan Kebudayaan, 2021)
For the history of human civilization, various outbreaks of viruses and diseases have occurred. One of the epidemics was the leprosy in the Dutch East Indies which increased sharply in the first half of the 20th century. People became victims of this epidemic, including children. Unfortunately, not many academics placed children as the focus on studies of leprosy. Due to this background, this study discussed children on epidemic of leprosy in the early 20th century. This study was conducted using the historical method, with colonial newspapers as the primary source. The results showed that children in the Dutch East Indies were infected with the leprosy from their parents who had previously been infected. The presence of children leprosy infected was considered to disturb the comfort of the surrounding environment, thus causing a number of polemics in the society. There were many demands to separate them from their surroundings and to prohibit them to go to school. To overcome this polemic, various philanthropic acts emerged to pay attention for children who have been leprosy infected. The philanthropic acts from Europe and the local doctors provided services for children leprosy infected by establishing hospitals and special foundations for them.